THE EFFECT OF SELF EFFICACY, ORGANIZATIONAL CULTURE AND WORK MOTIVATION ON JOB SATISFACTION OF LANGKAT REGENCY AGRICULTURE AND FOOD SECURITY SERVICE OFFICE. - Filzah Zarifah Zahra Harahap; Faisal Matriadi; A. Hadi Arifin; Nurmala (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2024)
This study aims to determine the effect of self efficacy, organizational culture and work motivation on job satisfaction of Langkat Regency Agriculture and Food Security Service Office. The population of this study was all of the employees of Langkat Regency Agriculture and Food Security Service Office, they were 75 employees. This sampling technique used saturated sampling, used primary data obtain through questionnaires, used multiple regression method. The data in this analysis were processed using the Statistical Program for Product and Service Solution (SPSS) version 22. The result of this study indicated that there was a positive and significant effect between self efficacy, organizational culture and work motivation on job satisfaction of Langkat Regency Agriculture and Food Security Service Office.